Scientific Approaches in the Teaching of English to Grade 7 Students - Jainal Abidin (Language-Edu, 2019)
The purpose of this research is to know the preparation, processing and assessment of scientific approach in teaching the English language for students’ grade 7 level of Islamic Junior High School. The design of this study is a case study with a qualitative approach. The subject of this research is two English teachers who teach the English language in MTsN Nganjuk. Data collection in this study by conducting observations, learning documents, and conducting semi-structured interviews. The findings: 1) Teachers already working to continuously improve the preparation methods and instruments of learning that can be assessed as an indication of success in the implementation of Curriculum 2013, especially in grades 7 MTsN Nganjuk. 2) Teachers already tried the maximum to implement the appropriate lesson plans written and well though not intensive, teachers have developed competence spiritual students, social and skills through giving some advice, interaction and learning activities are inserted when explained. 3) Teachers have been implemented the assessment process in MTsN Nganjuk. In terms of assessment, the teachers used two types of assessment, namely, authentic and non-authentic.